Perception of faculty and students at the State University of Santa Cruz (UESC) TechnologyTransfer Office (TTO) - Costa, Aldair de Jesus; Araújo, Aline Patrícia Mano; Silva, Brena (Brazilian Journal of Production Engineering, 2025)
Innovation can be considered as the development of a new product, service, and/or method. In Brazil, two legal frameworks define innovation: Law No. 10,973 of December 2004, and Law No. 11,196 of November 2005. These are important legal instruments for promoting innovation and regulating Science and Technology Institutes (STIs) and Technological Innovation Centers (TTO). This study aimed to analyze the perception of students and professors of the postgraduate program at the State University of Santa Cruz (UESC) regarding the existence and role of the Technological Innovation Center of the State University of Santa Cruz. The research method used was a survey. The study had a population of 946 individuals, 666 students, and 280 professors. However, only 79 participants answered the questionnaire. Data analysis showed that 59% of respondents were unaware of the work that the TTO performs. This result suggests the existence of a communication barrier. Understanding this barrier can help the TTO increase its visibility and impact, not only within the academic environment but also in the community at large. The research reveals that, although legislation highlights its importance, practical recognition of its role is still lacking. The divergence in perception between students and professors’ points to a need for organizational change at the university since 59% of participants are unaware of the functions of the TTO, which can discourage engagement in innovative initiatives.